2021
DOI: 10.3389/fmicb.2021.643719
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Concentrations of Sulfonamides Can Alter Bacterial Structure and Induce Diatom Deformities in Freshwater Biofilm Communities

Abstract: Since the early 1920s, the intensive use of antibiotics has led to the contamination of the aquatic environment through diffuse sources and wastewater effluents. The antibiotics commonly found in surface waters include sulfamethoxazole (SMX) and sulfamethazine (SMZ), which belong to the class of sulfonamides, the oldest antibiotic class still in use. These antibiotics have been detected in all European surface waters with median concentrations of around 50 ng L–1 and peak concentrations of up to 4–6 μg L–1. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 67 publications
6
29
0
Order By: Relevance
“…Whereas βglucosidase and phosphatase activities (Figures 2A,C) were not sensitive to low levels of SMZ (<4 µg SMZ kg −1 dw), leucine aminopeptidase activity (Figure 2B) was found to be transiently stimulated at both low and high levels of SMZ exposure after 14 days of exposure (p < 0.05). This transient microbial response had also been observed previously by Kergoat et al (2021) in periphytic biofilms exposed to mean SMZ concentrations ranging from about 106 to 157 ng SMZ L −1 . To our best knowledge, there is no other published study investigating the chronic effect of SMZ on the leucine aminopeptidase activity.…”
Section: Environmental Concentrations Of the Tested Sulfonamides Affected Sediment Microbial Community Functions Differentlysupporting
confidence: 85%
See 4 more Smart Citations
“…Whereas βglucosidase and phosphatase activities (Figures 2A,C) were not sensitive to low levels of SMZ (<4 µg SMZ kg −1 dw), leucine aminopeptidase activity (Figure 2B) was found to be transiently stimulated at both low and high levels of SMZ exposure after 14 days of exposure (p < 0.05). This transient microbial response had also been observed previously by Kergoat et al (2021) in periphytic biofilms exposed to mean SMZ concentrations ranging from about 106 to 157 ng SMZ L −1 . To our best knowledge, there is no other published study investigating the chronic effect of SMZ on the leucine aminopeptidase activity.…”
Section: Environmental Concentrations Of the Tested Sulfonamides Affected Sediment Microbial Community Functions Differentlysupporting
confidence: 85%
“…Most of the microbial activities increased over time, reflecting microbial growth and activity. As previously reported in several studies assessing the effects of SMX and SMZ on aquatic microbial biofilms (Yergeau et al, 2010(Yergeau et al, , 2012Kergoat et al, 2021;Paumelle et al, 2021), the functional responses observed in the present experiment varied markedly according to the antibiotic tested.…”
Section: Environmental Concentrations Of the Tested Sulfonamides Affected Sediment Microbial Community Functions Differentlysupporting
confidence: 74%
See 3 more Smart Citations